Some Empirical Evidence on the Stability of Money Demand in Kenya - Kiptui, Moses C. (International Journal of Economics and Financial Issues, 2014)
This study examines the stability of the demand for money in Kenya owing to conflicting results derived from previous studies which have cast doubt on the relevance of monetary targeting. Bounds testing techniques are applied and an error correction model estimated. Demand for broad monetary aggregates is shown to be stable. Moreover, the real income elasticity estimates derived in the analysis are reasonably within the range expected in the Baumol-Tobin framework while the interest rate (Treasury bill rate) elasticity is in the expected range of -0.1 to -0.5. An uncertainty variable incorporated in the model is found to have positive effects on demand for broad monetary aggregates particularly M2 money demand, implying that uncertainty drives economic agents to subsequently switch to relatively liquid assets. The finding that demand for broad monetary aggregates is stable can be interpreted to mean that monetary targeting remains relevant in the Kenyan context. Keywords: Money demand; stability; monetary policy formulation JEL Classifications: E41; E52